Resonance Energy Transfer Between Luminescent Quantum Dots and Diverse Fluorescent Protein Acceptors - Medintz, Igor L. (2009)
We characterized the resonance energy transfer interactions for conjugates consisting of QD donors self-assembled with three distinct fluorescent protein acceptors: two monomeric fluorescent proteins, the dsRed derivative mCherry or yellow fluorescent protein and the multi-chromophore b-phycoerythrin light harvesting complex. Using steady-state and time-resolved fluorescence, we showed that nonradiative transfer of excitation energy in these conjugates can be described within the Förster dipole-dipole formalism, with transfer efficiencies that vary with the degree of spectral overlap, donor-acceptor separation distance and the number of acceptors per QD. Comparison between the quenching data and simulation of the conjugate structures indicated that while energy transfer to monomeric proteins was identical to what was measured for QD-dye pairs, interactions with b-phycoerythrin were more complex. For the latter, the overall transfer efficiency results from the cumulative contribution of individual channels between the central QD and the chromophores distributed throughout the protein structure. Due to the biocompatible nature of fluorescent proteins, these QD-assemblies may have great potential for use in intracellular imaging and sensing.